A study on the performance of technology transfer units - Romero, Fernando (2015)
Universities are increasingly institutionalizing activities related to technology transfer and one of the main institutional mechanisms that has emerged is the “technology transfer unit” (TTU). Many of them are focusing their activities on the management of the university intellectual property. Studies have investigated factors that seem to affect their performance, but few have looked in detail at internal procedures and techniques that are used in their processes related to technology evaluation and licensing. The aim of this paper is to provide a comprehensive overview of some of the several steps that comprises the processes regarding technology evaluation and licensing, providing an analysis of the critical issues that affect each step of the process. A review of the literature was made, complemented with interviews to seven university TTUs, which was used as a check and a complement to the literature review and as way of perceiving from an insider perspective, the problems and issues that this paper wants to emphasize and to state clearly.